Seismic Retrofit of Reinforced Concrete Frames with Diagonal Prestressing Cables - Molaei, Ali (Université d'Ottawa / University of Ottawa, 2014)
A large number of building inventory in Canada and elsewhere in the world consists of non-ductile reinforced concrete frames, with or without masonry infill panels. These structures suffer damage when seismic force demands are higher than their force capacities. Therefore, seismic retrofitting of such frame buildings for drift control remains to be a viable option for improved building performance. A retrofit methodology has been developed in the current research project, which involves diagonal bracing of frames with prestressing strands. An experimental research project has been conducted to assess the effectiveness of diagonal prestressing in non-ductile reinforced concrete frame buildings. The experimental program consists of two large-scale single-bay single-storey reinforced concrete frames, with a height of 3.0m and a span length of 3.5 m. The frames were designed and built to reflect the 1960’s practice in Canada, without the seismic requirements of current building codes, and hence are seismically deficient. They were retrofitted with diagonally placed prestressing strands, having two different areas of steel, prestressed to 40% of the strand capacity. One of the frames was retested after the failure of the strands, with a new set of strands without any prestressing, forming the third test. The results indicate that lateral bracing reinforced concrete frames with high-strength prestressing strands is an effective strategy for controlling lateral drift and hence potential damage in buildings during strong earthquakes. Prestressing of the strands increases initial stiffness, as compared to non-prestressed cables, and provide superior performance. The area of diagonally placed steel (including the number of strands) and the level of initial prestressing depend on the required level of upgrade in the building in terms of seismic force requirements. The design procedure recommended in this thesis may be employed for implementing the technology. The thesis presents the details of the experimental program, and the test results. It also provides analytical verification of the approach, with a step-by-step design procedure.
Keywords: Prestressing Cables; Seismic Retrofit; Concrete Frames Retrofit